A hierarchical dispatch method for tri-level integrated thermal and power systems. (December 2021) - Jiang, Tuo; Min, Yong; Zhou, Guiping; Chen, Lei; Chen, Qun; Xu, Fei; Ye, Qixin
Highlights: Models of district heating systems and combined heat and power plants are discussed. Hierarchical dispatch is used for tri-level integrated thermal and power systems. Solution methods for implementing the hierarchical dispatch method are proposed. Abstract: Owing to the increase in the installed capacity of combined heat and power (CHP) units, electric power systems (EPS) and district heating systems (DHS) couple more strongly by CHP plants at the physical level to produce EPS–CHP plant–DHS tri-level integrated thermal and power systems (ITPS). However, various ITPS components are traditionally operated by different enterprises in an uncooperative mode, which results in non-optimal operational conditions and a serious wind curtailment problem. In this study, a generalized hierarchical dispatch method based on the day-ahead economic dispatch problem for a tri-level ITPS is developed to coordinate its different constituents. It decomposes the ITPS economic dispatch problem into an EPS sub-problem, a DHS sub-problem, and a CHP plant sub-problem. The lower level systems transfer so-called feasible region of boundary variables (FRBV) and optimal function of boundary variables (OFBV) to the upper level systems. After that, the upper level systems compute the optimal values of the boundary variables based on the FRBV and OFBV and transmit them to the lower level systems. The nonlinear CHP plant sub-problem is linearized first and then solved utilizing a grid-based method. The results of case studies show that the relative errors of applying the linearization approximation to the nonlinear terms in the CHP plant sub-problem do not exceed 3%. Furthermore, while the solution obtained by the hierarchical dispatch method is less optimal than the ideal situation, the deviations of the optimal values computed for different stages of the heating seasons do not exceed 1.5%. Finally, the simulation data produced for a real urban tri-level ITPS indicate that the hierarchical dispatch method is very efficient for practical application.